Lost in Translation - Burton, Robert A. (Cambridge quarterly of healthcare ethics, 2024)
"Scleroderma," the rheumatologist said after examining my stiff swollen arms and legs. "Unfortunately, given your biomarkers, it’s likely to get worse before it gets better, but you never know." She gave a quick rundown of what I might expect—rapidly progressive skin and joint tightening, GI symptoms, high likelihood of multi-organ involvement…. "Let’s hope for the best." She paused, then asked if I had any questions.